An Improved Approach to Design A Photovoltaic Panel - Murari Lal Azad; Pradip Kumar Sadhu; Soumya Das; Biplab Satpati; Anagh Gupta; P Arvind; Riya Biswas (Institute of Advanced Engineering and Science, 2017)
In this paper, modeling and simulation of the solar photo-voltaic (PV) power generator is observed using Matlab-Simulink environment. The study the fore-mentioned photovoltaic systems in an efficient manner the knowledge of I-V and P-V characteristics is a prerequisite. Effect of environmental parameters of temperature and irradiance variations could also be observed from simulated characteristics.